Pengembangan Media Pembelajaran Berbasis Google Sites pada Mata Pelajaran Teknologi Layanan Jaringan - Selviyanti, Erna; fariz, Ahmad (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2024)
The Government requires the classroom learning system to be replaced with learning at home through an online system. This research was conducted to develop learning media based on Google sites in the subject of network service technology. This research was conducted to see the feasibility of the developed Google sites-based learning media. The method used in this research is Research and Development with ADDIE development were Analysis, Design, Development, Implementation, and Evaluation. The development stage involved four validators as media experts and materials experts to assess the feasibility of media and materials. The implementation phase was limited to involving 34 students of class XII Computer Network Engineering. Collecting data using validation questionnaires, response questionnaires and interviews. Data analysis techniques are descriptive qualitative and quantitative. The results of this study are learning media products based on Google sites in the course of network service technology. One of the materials discussed is a firewall on a VoIP network. The results of the feasibility test show that the Google sites-based learning media is feasible to use. This is based on the validation of media experts who obtained an average result of 97,3% in the “strongly agree” category, material expert validation obtained an average result of 88,6% in the “strongly agree” and based on the results of the questionnaire students obtained an average result of 92,86% in the “strongly agree”. This indicates that all aspects assessed are in the very good category.